Wear Performance of Wire Arc AM SS 316L Plate For Different Thermal History Regions - Abdulrahman Alrumayh (Tribology in Industry)
The development of metal Additive Manufacturing AM processes has become promising for different applications and sectors, especially 316L austenitic stainless steel. Compared with polymer AM which has reached near maturity in process parameters and product properties, metal AM processes have enormous areas for research. Wire Arc AM (WAAM) has a high deposition rate and high heat input, which changes material properties in many ways. For example, wear rate has been studied in AM and WAAM, especially for different materials and parameters. This study aims to investigate the difference between the wear behaviors for different regions in WAAM printed samples. The regions have different thermal cycle histories and different hardness levels. A sample was printed by WAAM and prepared for wear test measurement. There are two selected areas, the inter-layer IL, and the middle of the layer IM which have different thermal cycles. The coefficient of friction COF, COF slope, Friction force, volume loss and mass loss, and hardness were measured and calculated for these two areas. The results show that the IL areas have lower COF, negative COF slope, and lower hardness than other areas. That can be the result of the thermal cycle which affects the residual stress.